2015
DOI: 10.1108/jcm-02-2014-0877
|View full text |Cite
|
Sign up to set email alerts
|

Does religion influence consumers’ green food consumption? Some insights from Malaysia

Abstract: Purpose – This paper aims to examine whether Muslim and non-Muslim consumers give different importance to green food consumption. Design/methodology/approach – Data were analysed using means comparison and multiple discriminant analysis across a sample of 700 students in a public higher learning institution in the Federal Territory of Labuan, Malaysia, using the convenience sampling technique. Findings – Empirical results via multiple discriminant analysis discovered that imperative aspects such as sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 56 publications
5
32
1
Order By: Relevance
“…Religious beliefs influence consumer psychology and behaviour towards shopping for and consumption of food. Religious beliefs and practices are positively associated with healthy food choices as well as a healthy lifestyle [19][20][21][22]50]. Suki and Suki [21] revealed that Muslim consumers were specific regarding shopping for and consumption of food products that comply with Islamic dietary laws and practices.…”
Section: Religious Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Religious beliefs influence consumer psychology and behaviour towards shopping for and consumption of food. Religious beliefs and practices are positively associated with healthy food choices as well as a healthy lifestyle [19][20][21][22]50]. Suki and Suki [21] revealed that Muslim consumers were specific regarding shopping for and consumption of food products that comply with Islamic dietary laws and practices.…”
Section: Religious Beliefsmentioning
confidence: 99%
“…Religious beliefs and practices are positively associated with healthy food consumption as well as healthy lifestyle. The religious beliefs, rituals and values influence consumer psychology and behaviour towards purchase intention and consumption of convenience food [18,21,22]. In recent years, ethical values have emerged as one of the most important issues in the context of shopping for and consumption of convenience food.…”
Section: Introductionmentioning
confidence: 99%
“…Research exploring determinants and obstacles of consumer ethical predispositions, intentions, and behaviors has generally neglected the potential of religiosity (Graafland, ); research on environmental predispositions, intentions, and behaviors (to be considered within the ethical domain) makes no exception, despite clear suggestions in this sense (Mohd Suki & Mohd Suki, ). This lack of attention appears quite surprising, as—especially for some consumption contexts—religiosity and environmental predispositions both appear powerful determinants of consumer ethical intentions and behaviors, namely environmentally conscious.…”
Section: Introductionmentioning
confidence: 99%
“…The literature devoted extensive attention to religious influences on consumers in Muslim markets over the last decades [17,[41][42][43]. Consumers' cultural affinities and religious inclinations can influence the choice of the product that suits their religion or culture.…”
Section: Literature Reviewmentioning
confidence: 99%